Economic inequality in Malaysia: the enemy within - Abd. Rahim, Shafinah Begum (2015)
The worsening inequalities across and within many countries have been an important part of the discussions among the international community in general and welfare economists in particular. The frequency of the recent economic crises across the globe had demonstrated that certain social groups are the hardest hit and disabled from recovering satisfactorily, despite swift national efforts and regional support. This research paper is part of a larger project viewing the current inequalities prevalent in Malaysia from a normative perspective through the lenses of Islamic Economics. It is aimed at providing complementary policy prescriptions in managing the widening socio-economic inequalities between the different marginalized groups. Given the conceptual nature of this research work, the emphasis remains in the critical literature reviews and latest report findings, both national and international. The ultimate objective of this study is to better understand the reality of economic inequalities and their long-term adverse effects on society perceived as vulnerable. Thus the main concern of the present work is to be clearly aware of the dangers of socio-economic inequalities and the various alternatives existing under the Islamic Economic System in managing inevitable inequalities. Key findings of this research paper include the recent relevant evidences of increasing economic inequality globally and Malaysia, the need for the stakeholders in Malaysia to begin considering the implications of economic inequalities critically and the effective application of several readily available schemes and tools in Islamic economics.